QUALITY OF EDUCATIONAL ACTIVITY: CURRENT PROBLEMS OF DEFINITION AND SUPPLY - Вінецька, Роза Михайлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: to highlight the modern problems of determining and ensuring the quality of educational activities and suggest ways to solve them. Methods of research: general scientific and special methods - epistemological, comparative-historical, sociological and hermeneutical. Results: the role of quality management principles for the development and implementation of a quality management system for education was determined; defined criteria for forming a list of principles is advisable to implement taking into account the general provisions on the introduction of a quality management system and the specifics of the subject of quality management - educational activities. A list of these principles is defined. Discussion: the problem of quality management education from the standpoint of predominantly the sciences of public administration, pedagogy. The article highlights current problems in determining and ensuring the quality of educational activities and proposed ways to solve them. The necessity of development and implementation of the quality management system of educational activity with the account of the peculiarities of the management level of the functioning of the system - national, regional, local, and local - is substantiated. The necessity of taking into account the formation of the quality management system of the peculiarities of types of education, forms of education, educational and qualification level of higher education is pointed out. The list of principles of quality management of educational activity, which should be general for all levels of the quality management system, is proposed. It is substantiated that the principles of quality management are of paramount importance for the development and implementation of a quality management education system. It is proved that formation of the list of principles is advisable to take into account the general provisions on the introduction of a quality management system and the specifics of the subject of quality management - educational activities. Therefore, it is attributed to the following principles: continuous monitoring of the implementation of the education development strategy in Ukraine; dissemination of discovered stories in the implementation of the strategy at all levels of education management; formation of a quality management system for educational activities at all levels of education management and others.